Splitting the sḏm.n⸗f? A Discussion of Written Forms in Coffin Texts: Part 1 - Stauder, Andréas (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
This is the first part of a study discussing the written forms of II.red (e.g. Ꜣmm ) in Coffin Texts adduced in support of a recent hypothesis of two morphologically distinct forms of the sḏm.n⸗f . As a result of a review of each individual written form, it is concluded that none supports the hypothesis (just as none contradicts it). The first part of the argument centers around how verbal stems are represented in writing, in II.red-ult.n , II.red-ult.Ꜣ , and II.red-ult . m . Early New Kingdom spellings of the same verbs are also reevaluated. (The second part of the study is to appear in the next issue of this journal.)